Speaking Birds and Cosmic Kites: Belief Narratives and Conspiracy Theories Regarding Latin American Political - Maria Palleiro (Transcript: An e-Journal of Literary and Cultural Studies, 2023)
This article deals with conspiracy narratives regarding two deceased Latin American leaders from Venezuela and Argentina, Hugo Chávez and Néstor Kirchner. These narratives, circulating on the Internet, are supported by allusions to ritualized communications with the dead, such as the supernatural apparition of Chávez as a speaking bird and of Kirchner as a “cosmic kite.” Such symbols are used as argumentative strategies to legitimate political programs, in narratives whose rhetorical construction is based on a synecdochic logic connected with the global threats to local cultures. These discourses show a folklorization process of these political figures, presented as emblematic metaphors of local identities rooted in the traditional past.